Implementasi Discharge Planning dan Kunjungan Ulang Kasus Nifas Dengan Preeklampsia - Yusniar Rahajeng, Agtus; Anis, Wahyul; Wittiarika, Ivon Diah; Andriyanti, Andriyanti (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Background: Preeclampsia during the postpartum period is one of the biggest contributors to maternal morbidity and mortality. The importance of discharge planning and good monitoring during return visits in postpartum cases with preeclampsia will have a positive impact in reducing morbidity and mortality due to postpartum hypertension complications. Objective: The purpose of this study was to examine and describe the implementation of discharge planning and return visits for postpartum cases with preeclampsia in one of the Type B Hospitals in Surabaya and the Surabaya City Community Health Center. Method: This study used a qualitative design with a phenomenological approach. Data collection was carried out through in-depth interviews and observations. The sample size was 18 informants, namely 11 midwives and 7 postpartum mothers with preeclampsia, with purposive sampling. Results: The results of the study found several obstacles in the implementation of discharge planning and return visits for postpartum cases with preeclampsia. The implementation of discharge planning, postpartum services and return visit schedules were not all carried out according to service standards, so there was no two-way communication between the Hospital and the Community Health Center. Conclusion: Implementing appropriate discharge planning and postpartum care serves as a benchmark for service quality and represents continuity of care in midwifery care, particularly for postpartum mothers with preeclampsia. Evaluation of any identified challenges is necessary to ensure optimal service delivery.